Nauczanie Jana Pawła II oraz Kościoła katolickiego dotyczące zagadnień etycznych życia rodzinnego i partnerskiego a poglądy na ten temat łódzkiej młodzieży akademickiej - Śmigielski, Witold (Annales. Etyka w Życiu Gospodarczym, 2011)
Evaluating demographical changes in Poland and Europe at the turn of 20th century, researchers more often use the expression „family crisis”. The increase in the number of divorces and in the number of extra-marital births, prevalence of pre-marital cohabitation, as well as its increased acceptance in the society and the increase in the scope of voluntary childlessness make up such an approach to the situation. This article presents and discusses the results of a survey concerning ethical matters of family life conducted in April 2010 amongst students of Lodz’s colleges. The responses were contrasted with the declared influence of Pope John Paul’s II pontificate. A vast majority of students claim to decide upon religious wedding while entering into marriage. They also declare bringing up their potential off springs in catholic tradition. The students of Lodz are also critical of abortion. It needs to be highlighted that in almost all aspects of family life people, who declared a positive influence of the teaching and life of the Polish Pope on their behaviour, more often than others supported the teaching of Roman Catholic Church. On the basis of the conducted survey it may be noticed that the students of Lodz remember about the Polish Pope and his teaching, however, do not support all of his views as far as family life is concerned. Also the majority of the students would say they belong to „the generation of JPII”.